A simple carbon fiber heating wire design method for preventing ice accretion on stay cables. (June 2022) - Pei, Yaoyao; Luo, Zhenyuan; Xiao, Henglin; Chen, Zhi; Zhou, Xinlong; Yang, Zhiyong
Abstract: In cold weather, the outer surface of stay cable sheaths easily freezes. When the ambient temperature increases, the ice on the surface melts easily, and there is a risk of falling ice at high altitudes. In this paper, a simple design method is proposed that uses carbon fiber heating wires to prevent the icing of stay cables. Conventional indoor tests and numerical simulations of heat conduction are carried out for a sheath with a single diameter, and the number of heating wires required for different diameter sheaths is obtained. Taking the stay cable sheath of the Qingshan Bridge in Wuhan as an example, when the diameters of the heating wire and the stay cable sheath are 6 mm and 200 mm, respectively, the temperature rise rule of the heating wire, the calibrated heating power and the convective coefficients are obtained through tests and numerical simulations. At an ambient temperature of 4 °C, thread-like ice formed in the arc range of 0.314 m on the surface of the sheath. The critical non-icing temperature required by the heating wire during preheating to ensure that the sheath surface does not freeze is 1.5 °C.